Signature Of Unwanted Signal Due To Induced Voltage at PV Solar By Lightning Strike - Abdul Rahim, Nur Hidayu (2016)
The recent advancement of renewable energy sources especially photovoltaic (PV) system has resulted in outdoor installations of large power stations. Therefore, the PV system may be exposed to risky conditions such as the lightning strike activities that are generated by induced overvoltage. The induced overvoltage of lightning has a high tendency to inject the unwanted signal to the solar panel as well as to the cable of the solar system. Improper protection scheme of PV system installation may affect the overall system performance will harm the electrical apparatus especially the sensitive devices. The above problematic issue leads to an investigation on the effect of induced voltage to the PV system. The experimental work is conducted to analyse the effects of different cable parameters on the induced voltage due to the simulated lightning strike. The secondary study is about the investigation of unwanted signal behaviour due to the induced voltage under different arrangement of solar panel through three different transmission line cables namely the normal transmission line (non-twisted cable), the twisted cable and the coaxial cable. The results of the study show the existence of unwanted signal propagating on the solar panel proportionally with the distance of the solar panel and the lightning impulse source. The conducted experiment has proven that the magnitude of the induced voltage could be reduced proportionally with the studied distance by selecting the suitable types of cable connection to the PV system. In the future, this thesis could guide the proper protection scheme for PV system installation such as the method of a proper cable shielding technique and coordination of surge protection device (SPD).